Analysis of Mathematical Creative Thinking Abilities of High School Students in West Bandung Regency - Nindra Giandra Tamirrino; Heris Hendriana; Wahyu Hidayat (IKIP Siliwangi, 2023)
The rapid development of technology requires creative human resources to solve various mathematical problems. The importance of thinking creatively is contained in the Graduate Competency Standards (SKL). This study aims to determine the mathematical creative thinking skills of high school students in West Bandung using sequence and series materials. The research method used is the descriptive qualitative research method. The study was conducted on 35 class XI students at a high school in West Bandung. The instrument used is four items about the ability to think creatively on the material sequences and series. The research was conducted in the odd semester of the 2022-2023 school year. The results showed that the percentage of flexibility indicator questions was 61.143%, which means most students can work on questions with the flexibility indicator. The rate of fluency indicator items was 52%, the percentage of originality indicator items was 43.169%, and the elaboration indicator was 40%. These results show that the elaboration indicator has the rate percentage compared to other indicators of creative thinking ability. The study’s results concluded that the creative thinking skills of high school students in West Bandung Regency were still low, with a percentage of 49.19%. Researchers recommend using interactive learning media such as e-LKPD to improve mathematical creative thinking abilities.